Adjustment of patterns of women’s trousers on the base of the lower body - Thi Nguyen, Mong Hien (BOHR International Journal of Operations Management Research and Practices, 2023)
This article presents the influence of female lower body characteristics as a waist position to the bottom of the foot on the design of women’s trousers. First, the author designs patterns for people with straight legs. Second, the product will wear on people with bow legs, X-legs, and people who have big waists and small thighs. Third, the author analyzes the fit of each pattern in every sample and gives directions for pattern correction. Finally, the samples are sewn again until they fit samples and are not wrinkles. The anthropometric theoretical research method is used in the product fit analysis. The theory designs trousers pattern that is used to design patterns for people who have straight legs. The experimental research method is used to conduct actual surveys on 40 people from four groups with different lower body parts through the Likert scale for five evaluation criteria on five levels. The survey results are analyzed on the SPSS software. The results show that Cronbach’s alpha index is over 0.7. Research has made practical contributions in the field of garment product design as well as consulting customers when buying and selling clothes.